2021
DOI: 10.1155/2021/6616062
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Inflammatory and Tumour Markers in Small-Duct Subtype Intrahepatic Cholangiocarcinoma after Curative-Intent Resection

Abstract: Intrahepatic cholangiocarcinoma (ICC) is characterised by heterogeneity, and it can be subdivided into small-duct and large-duct types. Inflammatory and tumour markers could effectively predict prognosis in many cancers, but no similar studies have been conducted in the histological subtypes of ICC. A total of 102 and 72 patients with ICC undergoing curative-intent resection were retrospectively subclassified into large-duct and small-duct types by chemical staining, respectively. The prognostic value of infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The remaining 111 studies were further vetted for eligibility after the titles and abstracts were reviewed. Ultimately, 20 studies were included in the analysis [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 111 studies were further vetted for eligibility after the titles and abstracts were reviewed. Ultimately, 20 studies were included in the analysis [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies identified the PLR as an independent predictor for impaired OS in patients with CCA [ 22 , 28 , 29 , 33 , 34 , 36 , 38 , 41 ], while the PLR was not prognostic for OS in twelve studies [ 23 , 24 , 25 , 26 , 27 , 30 , 31 , 32 , 35 , 37 , 39 , 40 ]. The combined analysis of all twenty publications showed that the PLR values higher than the defined cut-off values predicted a worse OS (HR = 1.14, 95% CI = 1.06–1.24, p < 0.01) with high heterogeneity (I 2 = 55%, p < 0.01, Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 32 publications related to OS, 19 original papers reported that NLR was an independent predictor for impaired OS 18 , 20 , 23 27 , 32 34 , 38 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 15 publications which reported DFS, 7 cohort studies showed that NLR was an independent predictor of reduced DFS in patients with CCA 18 , 23 , 39 , 40 , 42 , 43 , 48 , whereas 7 publications observed no significant relationship between NLR 19 , 25 , 30 , 33 , 35 , 36 , 44 and DFS and one study showed NLR was a prognostic for a longer DFS 47 . The pooled analysis of all studies showed that a higher NLR level was associated with impaired DFS (HR 1.39, 95% CI 1.17–1.66, p < 0.01) with high heterogeneity (I 2 = 73%, p = 0.02, Fig.…”
Section: Resultsmentioning
confidence: 99%